The Effect of Transformational Leadership and Work Engagement on Teacher Performance: Mediating Role of Innovative Work Behavior - Edy Sukendar; Achmad Mohyi; Rizki Febriani (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine the effect of transformational leadership and work engagement on teacher performance by positioning innovative work behavior as a mediating variable. The study seeks to clarify the mechanism through which leadership and engagement influence performance in the context of Islamic elementary schools. A quantitative approach was employed using a survey method. Data were collected through questionnaires distributed to all teachers and staff at SD IT Al Qudwah in Tugumulyo District, Musi Rawas Regency, South Sumatra. A total of 100 respondents participated in the study using a saturated sampling technique. The data were analyzed using path analysis with SmartPLS to test both direct and indirect relationships among variables. The results indicate that transformational leadership and work engagement do not have a direct effect on teacher performance. However, both variables significantly influence innovative work behavior. Furthermore, innovative work behavior has a significant effect on teacher performance and mediates the relationship between transformational leadership, work engagement, and teacher performance. These findings highlight the importance of innovation-oriented behavior as a key mechanism in improving teacher effectiveness. This study contributes to the educational management literature by providing empirical evidence on the mediating role of innovative work behavior in the relationship between transformational leadership, work engagement, and teacher performance in Islamic school settings. The findings offer practical implications for school leaders to foster innovation as a strategic pathway to enhance teacher performance.